Vai trò của thái độ cá nhân, giảng viên và gia đình đối với động cơ học tập tiếng Anh của sinh viên Trường Đại học Thủ đô Hà Nội - Trần Thị Thơm, Trần Thị Thơm; Bùi, Minh Tuyên (Tạp chí Giáo dục, 2026)
In the context of globalization and international integration, English has increasingly become an essential tool for students’ academic pursuits and future professional activities. However, students’ motivation to learn English varies considerably due to the influence of multiple factors. This study aims to investigate the role of personal attitude, instructor influence, and family support in English learning motivation among students. A quantitative research approach was employed by administering a structured questionnaire to 201 students at Hanoi Metropolitan University. The collected data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 20.0. The results showed that personal attitude and instructor influence were significant positive predictors of students’ English learning motivation. However, family support was not a significant predictor of students’ English learning motivation. Based on the research findings, several implications are proposed to contribute to enhancing the English learning motivation of students at Hanoi Metropolitan University. This study opens up pathways for future research by incorporating additional variables that influence students’ English learning motivation; concurrently, the scope of investigation could be expanded to increase the explanatory power and generalizability of the research findings.